Sprawozdanie z II edycji Konkursu z Prawa Samorządu Terytorialnego zorganizowanego przez dr hab. Małgorzatę Ofiarską prof. US, Zespół Badawczy Prawa Finansowego Wydziału Prawa i Administracji Uniwersytetu Szczecińskiego oraz Koło Naukowe Prawa Finansowego „FiskUS” - Dawid Czesyk (Studia Administracyjne)
On January 11, 2024 in the Faculty of Law and Administration of the University of Szczecin was the second edition of the Local Government Law Competition. The competition was organized by dr hab. Małgorzata Ofiarska prof. US, Financial Law Research Team of the Faculty of Law and Administration of the University of Szczecin and the Financial Law Scientific Circle "FiskUS". The competition was open to students of the Faculty of Law and Administration of the University of Szczecin studying the subject: local government law in the academic year 2023/2024. In the second edition of the Local Government Law Competition, Ms. Amelia Skoczylas won, scoring the highest number of points (29). Second place (28 points) was taken by Mrs. Martyna Iwanek and Wiktoria Brewka, while third place (26 points) was taken by Mrs. Matylda Fisher and Mrs. Aleksandra Gwiazda. The winners were exempted from the obligation to take the exam in the subject Local Government Law. The winners also received material prizes, including books enabling them to expand their knowledge related to the functioning of local government.